Sistem Pantau dan Kendali Peralatan Listrik Rumah Berbasis Internet of Things (IoT) - Farid Farid; Nur Sultan Salahuddin (Universitas Islam Raden Rahmat, Malang, 2024)
The electrical energy monitoring and control system is infrastructure that provides users with the ability to not only monitor, but also regulate and optimize the use of electrical energy. Through this system, the latest information regarding electrical energy consumption can be accessed by users, enabling wiser decisions regarding energy savings. The research carried out combines two different research methods to achieve the stated objectives, namely descriptive research methods and experimental methods. Data analysis integrates data analysis using Blynk and programming via Arduino IDE, users can manage information collected from current and voltage sensors. The results of the research are IoT technology tools that can be used to monitor and control home electricity use. The measurement of electrical voltage in the design of the tool can be declared successful and has a fairly good accuracy value.